Antibiotic Resistance of Escherichia coli Isolate from Broiler Cecum and Organic Broiler Cecum - Septianita Eva Rozani; Maria Erna Kustyawati; Dewi Sartika; Subeki Subeki; Tanto Pratondo Utomo (JURNAL ILMIAH PETERNAKAN TERPADU, 2023)
This study aims to determine the level of antibiotic resistance of Escherichia coli bacterial isolates from broiler cecum and organic broiler cecum using the disc diffusion method on Muller-Hinton Agar as many as 10 cecum samples for each group.Collection of samples using purposive sampling method. Isolates suspected of being Escherichia coliwere further tested using Indole, Methyl Red Voges-Proskauer (MRVP), and Citrate (IMVIC) biochemical tests. E. coli isolates were further tested with the Antimicrobial Susceptibility Testing which aims to test antibiotic sensitivity. The results obtained from testing antibiotic resistance against Escherichia coli in broiler caecums showed a fairly high level of resistance to Gentamicin (70%), Ampicillin (100%), Cephalotin (100%), Nalixid Acid (86%), Streptomycin (80%), Erythromycin (100%), Oxytetracycline (80%), and the lowest was the antibiotic Chloramphenicol (30%), while the level of resistance in organic broilers showed Ampicillin (100%), Cefalotin (70%), Erythromycin (100%), the lowest resistance was Gentamicin (10%), Oxytetracycline (20%), Chlorampenicol (10%). Escherichia coli isolates obtained from the caecum of broiler and organic broiler showed a fairly high level of resistance. Conclusions of this study were resistance of Escherichia coli bacteria isolated from broiler cecum showed high results to almost all antibiotics except for chloramphenicol antibiotics, while resistance to Escherichia coli bacteria in organic broilers was lower than broilers but still showed a fairly high level of resistance, except for antibiotics Gentamicin, Nalixid acid , and chloramphenicol.